Relevansi dan Kontinuitas Pemikiran Islam Klasik dalam Intelektualisme Islam Melayu Nusantara - Ris'an Rusli; Y. Yanto (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2018)
This study aims to determine the relevance and continuity of classical Islamic thought in Nusantara Malay Islamic intellectualism, expected to be useful in adding to the treasures of the study of history and intellectual thought while also contributing to the preservation of scientific traditions in Indonesia. This study uses a type of qualitative research with a library research model with a historical approach. The data collection techniques in the study are heuristic techniques, verification, interpretation, and historiography. The results of this study conclude that first, the process of the intellectual tradition of Malay Archipelago Islam is inseparable from the process of transmission and diffusion of Islamic teachings and ideas always involving a kind of